Large amplicon droplet digital PCR for DNA‐based monitoring of pediatric chronic myeloid leukaemia. Issue 8 (14th June 2019) - Krumbholz, Manuela; Goerlitz, Katharina; Albert, Christian; Lawlor, Jennifer; Suttorp, Meinolf; Metzler, Markus
Abstract: Quantification of tumour‐specific molecular markers at the RNA and DNA level for treatment response monitoring is crucial for risk‐adapted stratification and guidance of individualized therapy in leukaemia and other malignancies. Most pediatric leukaemias and solid tumours of mesenchymal origin are characterized by a relatively low mutation burden at the single nucleotide level and the presence of recurrent chromosomal translocations. The genomic fusion sites resulting from translocations are stable molecular tumour markers; however, repeat‐rich DNA sequences flanking intronic breakpoints limit the design of high sensitivity PCR assays for minimal residual disease (MRD) monitoring. Here, we quantitatively evaluated the impact of repeat elements on assay selection and the feasibility of using extended amplicons (≤1330 bp) amplified by droplet digital PCR to monitor pediatric chronic myeloid leukaemia (CML). Molecular characterization of 178 genomic BCR‐ABL1 fusion sites showed that 64% were located within sequence repeat elements, impeding optimal primer/probe design. Comparative quantification of DNA and RNA BCR‐ABL1 copy numbers in 687 specimens from 55 pediatric patients revealed that their levels were highly correlated. The combination of droplet digital PCR, double quenched probes and extended amplicons represents a valuable tool for sensitive MRD assessment in CML and may be adapted to other translocation‐positive tumours.